Maxillary rehabilitation after complete destruction by fungal osteomyelitis - S M Balaji; Preetha Balaji (Wolters Kluwer Medknow Publications, 2019)
Treatment of uncommon fungal infection such as Rhinosporidiosis is challenging, especially when occurring in a non-immunocompromised patient in non-invasive form. Extensive involvement, extending into maxillary jawbone would need aggressive, chemotherapeutic and surgical approach. There are few reports of successful rehabilitation of maxillary jaw with dental implants after treatment of such fungal infection. After adequate medical treatment, the iliac graft and recombinant bone morphogenetic protein-2 was effectively utilized to reconstruct the lost maxillary bone. Later, dental implants were placed, that osseointegrated well.